Non-hydrolytic functions of acetylcholinesterase: the significance of C-terminal peptides - Greenfield, S; Zimmermann, M; Bond, C (Blackwell Publishing, 2008)
This review explores the possibility that acetylcholinesterase may play a pivotal, non-hydrolytic role in neurodegeneration. More specifically, C-terminal sequences of acetylcholinesterase may act as signalling molecules in key brain regions characteristically vulnerable to Alzheimer's, Parkinson's and motor neuron disease.